Knowledge of enhanced recovery after surgery and influencing factors among abdominal surgical nurses: a multi-center cross-sectional study. Issue 4 (4th July 2022) - Xue, Bing; Yu, Huidan; Luo, Xianwu
Abstract : Background: Enhanced recovery after surgery (ERAS) protocols are well established. Evidence describing nurses' knowledge of ERAS is limited. Aim : To assess surgical nurses' knowledge of ERAS and identify factors that correlate with knowledge level. Design: An anonymous cross-sectional survey via an online social platform was conducted in the abdominal surgical specialty of 40 hospitals in ten cities in China. Methods: Nurses of abdominal surgery in hospitals were enrolled in this study. A self-administered questionnaire that was reviewed by an expert panel was used to assess the knowledge of ERAS in nurses. A generalised linear regression analysis was used to assess factors associated with nurses' knowledge regarding ERAS. Results: Overall survey participation was 91.8% (2230/2430). The mean score of ERAS-related knowledge among abdominal surgical nurses was 12.10 (SD = 3.79). ERAS knowledge differed according to gender, age, education level, professional title, years of working, specialised working years, ERAS training experience, surgical department, and type of hospital ( p  < 0.05). Conclusions: Chinese nurses employed in abdominal surgical services need to improve the knowledge about ERAS protocols. Standardised training is recommended to improve nurses' ERAS-related knowledge, which can help nurses improve the quality of perioperative care and promote the recovery of patients.